ANALISIS KINERJA KEUANGAN BANK MENGGUNAKAN METODE RGEC (Studi Kasus Pada 3 Bank Milik Pemerintah Pusat Yang Terdaftar Di BEI Periode 2012-2014) - Sari, Indah Permata; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Banks were the financial institutions that play an important role in improving the economy of a country. Increasing competition among banks in practice many banks are less careful or deviate from the rules applicable. Elements that should receive particular attention is the financial performance of the bank. To assess the financial performance of one of them through the bank's financial statements. The financial statements also the media information about the health of the banking performance. To assess the soundness of banks in Indonesia, Bank Indonesia as the central bank has an important role in the national banking system in healthy banks, in order to achieve stability in the financial system of the bank.This research is descriptive quantitative research with the aim to identify and analyze the financial performance of the three (3) Bank Owned central government by using methods RGEC. The method of measuring the financial performance using ratios as indicators of NPL, IER, LDR, NPM, ROA and CAR on bank financial statements as primary data.Results of research conducted average yield ratio and placement of components ratings show PT. namely PT. Bank Mandiri (Persero) Tbk, the Year 2012 is categorized as "Very Healthy" (PK-1), in 2013 predicated "Very Healthy" (PK-1), 2014 is categorized as "Very Healthy" (PK-1), PT. Bank Rakyat Indonesia Agroniaga, The year 2012 is categorized as "Healthy" (PK-2), in 2013 predicated "Healthy" (PK-2), 2014 is categorized as "Healthy" (PK-2), and PT. Bank Rakyat Indonesia (Persero), the Year 2012 is categorized as "Very Healthy" (PK-1), in 2013 predicated "Very Healthy" (PK-1), 2014 is categorized as "Very Healthy" (PK-1), Keywords: Financial Performance, Methods of Analysis RGEC, NPL ratio, IER, LDR, NPM, ROA, CAR.